2020
DOI: 10.1002/pssa.202000015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Optical Properties of Stretchable Silicon Nanocrystal/Polydimethylsiloxane Nanocomposites

Abstract: Nanoparticle‐infused polymer composites have long been an area of interest due to the typically stabilizing effects they have on the mechanical behavior of the composites, as well as added functionalities such as reduced surface resistance. Newer applications of these nanocomposites include dispersing optoelectronically functional nanoparticles in polymer matrices, for example, including luminescent nanocrystals in rigid slabs for luminescent solar concentrating photovoltaics and electrochromic panels. Dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…[28][29][30][31] We recently published our research on the differences in neo-Hookean coefficient for nanocomposites of SiNCs and PDMS, based on surface functionality. 39 We found that the surface-functionalized SiNCs in the composite did decrease the neo-Hookean coefficient, but not as dramatically as the bare SiNCs. Because we saw a change in the mechanical behavior of the SiNCs and the surrounding PDMS dependent on surface functionality, we expected to see an effect of functionalization on the mechanical properties of the thin SiNC layers.…”
Section: Inuence Of Surface Functionalizationmentioning
confidence: 68%
See 1 more Smart Citation
“…[28][29][30][31] We recently published our research on the differences in neo-Hookean coefficient for nanocomposites of SiNCs and PDMS, based on surface functionality. 39 We found that the surface-functionalized SiNCs in the composite did decrease the neo-Hookean coefficient, but not as dramatically as the bare SiNCs. Because we saw a change in the mechanical behavior of the SiNCs and the surrounding PDMS dependent on surface functionality, we expected to see an effect of functionalization on the mechanical properties of the thin SiNC layers.…”
Section: Inuence Of Surface Functionalizationmentioning
confidence: 68%
“…Despite our ndings for the nanocomposites, our results here suggest that the functionalization does not change, mechanically, the particle-to-particle interaction. 39 We intend to continue to probe the dependence of the neo-Hookean coefficient based on the SiNC surface for ultra-thin layers, but as a direct comparison to the standard sample, we observed no difference.…”
Section: Inuence Of Surface Functionalizationmentioning
confidence: 80%
“…In the first step, the system (1) should be discretized as 𝑥 𝑘 = 𝑓 𝑐𝑙 (𝑥 𝑘−1 ) + 𝑤 𝑘−1 𝑦 𝑘 = ℎ(𝑥 𝑘−1 ) + 𝑣 𝑘−1 (26) with…”
Section: Extended Kalman Filter Algorithmmentioning
confidence: 99%
“…Recently, micro/nano-scale beams play significant roles in micro/nano-electromechanical systems (MEMS/NEMS) such as nanocomposites [26], micro-actuators [27], microresonators [28], and so on [29,30]. Nonlinear vibration is one of the most important problems in micro/nano-scale beams.…”
Section: Introductionmentioning
confidence: 99%
“…Farhangi et al investigated effect of fiber reinforced polymer tubes filled with recycled materials [16,17]. Izadi et al investigated effect of nanoparticles on mechanical properties of polymers [18,19,20]. Nunes and Moreira [21], in 2013, published a work that analyzes the simple shear state of an incompressible hyperelastic solid under large deformation by experimental and theoretical approaches.…”
Section: Past Researchmentioning
confidence: 99%